Expression of cancer/testis antigens in salivary gland carcinomas with reference to MAGE‐A and NY‐ESO‐1 expression in adenoid cystic carcinoma. Issue 2 (2nd June 2017) - Beppu, Shintaro; Ito, Yohei; Fujii, Kana; Saida, Kosuke; Takino, Hisashi; Masaki, Ayako; Murase, Takayuki; Kusafuka, Kimihide; Iida, Yoshiyuki; Onitsuka, Tetsuro; Yatabe, Yasushi; Hanai, Nobuhiro; et al.
Abstract : Aims: Cancer/testis antigens (CTAs) are detected in cancer cells but not in healthy normal tissues, with the exception of gametogenic tissues. CTAs are highly immunogenic proteins, and thus represent ideal targets for cytotoxic T‐lymphocyte‐mediated specific immune therapy. The aim of this study was to screen CTA expression in various types of salivary gland carcinoma and to clarify clinicopathological significance of MAGE‐A and NY‐ESO‐1 expression in adenoid cystic carcinomas (AdCCs) of the salivary gland, which is one of the most common salivary gland carcinomas, and usually has a fatal outcome. Methods and results: We used immunohistochemistry to examine the expression of four CTAs (MAGE‐A, NY‐ESO‐1, CT7, and GAGE7) in various types of salivary gland carcinoma ( n = 95). When carcinoma cases were divided into low‐grade and intermediate/high‐grade types, NY‐ESO‐1 and CT7 were expressed more frequently in intermediate/high‐grade carcinomas. We then focused on MAGE‐A and NY‐ESO‐1 expression in a large cohort of adenoid cystic carcinomas (AdCCs) ( n = 46). MAGE‐A and NY‐ESO‐1 were frequently expressed in AdCC; specifically, MAGE‐A was expressed in >60% of the AdCC cases. MAGE‐A expression and tumour site (minor salivary gland) were identified as independent risk factors for locoregional tumour recurrence. Conclusions: These findings suggest that CTAs may be expressed in a variety of salivary gland carcinomas, especially in those with higher histological grades. In addition, MAGE‐A, which is frequently expressed in AdCC cases, may be a useful prognostic factor for poorer locoregional recurrence‐free survival.